EFFECTIVENESS OF NARCISSUS LEAF EXTRACT (Crinum asiaticum L.) FOR THE TREATMENT OF CARP (Cyprinus carpio L.) JUVENILE INFECTED WITH Aeromonas hydrophila - Azizah, Zahrina; Mujtahidah, Tholibah; Armando, Eric (JURNAL AKUAKULTURA, 2025)
In fish farming activities, problems often arise that must be faced by farmers, the main factor causing the failure of fish farming efforts is the emergence of disease attacks. The type of disease that often attacks carp (Cyprinus carpio) is the bacteria Aeromonas hydrophila. Efforts made by farmers using artificial drugs or antibiotics. The use of antibiotics does not always have a positive effect; there are also negative effects. Therefore, natural, environmentally friendly handling is needed, and water lily leaf extract plants (Crinum asiaticum L.) are able to treat A. hyrophila infections in farmed fish. This study aims to determine the soaking of water lily leaf extract on the survival and optimal concentration that can reduce infection in carp juvenile (Cyprinus carpio). The research method used is an experiment with a Completely Randomized Design (CRD) consisting of 3 treatments and 3 replications. Treatment P1 (20 ml of water lily leaf extract), treatment P2 (40 ml of water lily leaf extract), and P3 (60 ml of water lily leaf extract). Data were analyzed using Analysis of Variance (ANOVA). If the results were significantly different, they were followed up with the Least Significant Difference (LSD) test. The results showed that the provision of water lily leaf extract (Crinum asiaticum L.) soaking had a very significant effect on the survival of carp (Cyprinus carpio) juvenile. The optimal concentration that can reduce A. hyrophila bacterial infection is in treatment P1 (20 ml) with the highest survival rate of 90%. Water quality during the study obtained a temperature value between 23-27.3 oC, pH between 6.9-8.45, and DO levels between 4.1-8.3 mg/l.